High-throughput pH monitoring method for application in dairy fermentations. Issue 4 (22nd November 2018) - Gutsal, Valery; Sieuwerts, Sander; Bibiloni, Rodrigo
Abstract : Optimization of dairy fermentation processes often requires multiplexed pH measurements over several hours. The method developed here measures up to 90 samples simultaneously, where traditional electrode-based methods require a lot more time for handing the same number of samples. Moreover, the new method employs commonly used materials and can be used with a wider range of fluorescence readers than commercial 96-well plates with optical pH sensors. For this application, a milk-like transparent medium is developed that shows acidification properties with dairy starters that are similar to milk. Combination of this milk-like medium and 3 fluorescent indicators allow precise measurements of pH in a range of 4·0–7·0. The new method showed much higher throughput compared to the benchmark electrode systems while being as accurate, as shown by successful application for a comparison of various dairy starter cultures and for optimizing the inoculation rate.